2020
DOI: 10.1177/0145482x20939469
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Motor Skills, Balance, and Physical Activity in Children with CHARGE Syndrome

Abstract: Introduction: Children with CHARGE syndrome often show delays in balance and motor skills due to multisensory impairments. Research also suggests that children with CHARGE syndrome have fewer opportunities to engage in physical activity. However, little research has examined the relationship among all of these variables. Thus, the purpose of this study was to examine the relationship between balance, motor skills, and physical activity. Methods: Participants consisted of 37 children with CHARGE syndrome aged 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Even when these children return from their medical leave, they are often excused from physical education for extended periods of time (Hilgenbrinck et al, 2020). These long absences from physical education and movement opportunities, which would typically improve their gross motor skill performance, may add to existing challenges with balance (Butterfield & Ersing, 1988;Haibach and Lieberman, 2013;Haibach-Beach et al, 2020;Perreault et al, 2020) and vestibular function (Möller, 2011) if they are not provided adapted and individualized services. These balance and vestibular challenges exacerbate the impact of the multiple surgeries and prolonged hospital stays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when these children return from their medical leave, they are often excused from physical education for extended periods of time (Hilgenbrinck et al, 2020). These long absences from physical education and movement opportunities, which would typically improve their gross motor skill performance, may add to existing challenges with balance (Butterfield & Ersing, 1988;Haibach and Lieberman, 2013;Haibach-Beach et al, 2020;Perreault et al, 2020) and vestibular function (Möller, 2011) if they are not provided adapted and individualized services. These balance and vestibular challenges exacerbate the impact of the multiple surgeries and prolonged hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…Early development in infants and children with CHARGE syndrome has revealed that they walk approximately 25 months later than children without disabilities (Dammeyer, 2012). Age of walking is an important milestone in motor development as it has been negatively associated with motor competence measures such as balance, throwing, running, sliding, and kicking (Perreault et al, 2020), and it is also associated with other important developmental outcomes, such as executive function (Hartshorne et al, 2007), adaptive behaviors (Salem- Hartshorne & Jacob, 2005), and language delays (Dammeyer, 2012).…”
mentioning
confidence: 99%
“…Specifically, we examined young children with CHARGE syndrome, the leading cause of congenital deafblindness [12]. Motor development is often significantly delayed in children with CHARGE syndrome due not only to sensory impairments, but motor impairments as well as environmental constraints, such as long hospital stays [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that children without disabilities were in childcare significantly more than children with CHARGE syndrome. These results are likely due to the medical needs of children with CHARGE syndrome at an early age [23,24]. Most daycares are typically not equipped to attend to the additional medical, functional, and communication needs of children with CHARGE syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation